The MIS 5.5 terraced deposit of Fosso del Cupo (Montecelio, Central Italy) and its Mousterian lithic assemblage: Re-evaluation of a nineteenth-century discovery. (15th December 2016) - Ceruleo, P.; Marra, F.; Pandolfi, L.; Petronio, C.; Salari, L.
Abstract: By means of a geomorphological study and the correlation with the geochronologically constrained terraced deposits of the greater area of Rome, we attribute to the aggradational phase during marine isotopic stage (MIS) 5.5 a terraced deposit firstly described in the earliest local geological reports of the 19th century, in which a small set of lithic artifacts and vertebrate fossil remains was recovered. After this correlation, the sedimentary deposit of Fosso del Cupo represents the only inland occurrence of an aggradational deposit of MIS 5.5 so far recognized in the area of Rome, where a rich record of lithic industries and faunal assemblages has been yielded by the sedimentary successions deposited in response to deglaciation during sea-level rises of MIS 15 through MIS 7. We have implemented the lithic and faunal assemblages through a collection during the geological survey performed in the area where the terraced deposit crops out. With an age tightly constrained around 125 ka, the lithic industry and the faunal assemblage from Fosso del Cupo, although limited in number, represent an important witness of the early development of the local Pontinian culture and should be considered a regional marker, which may concur to improve the knowledge on the Mousterian of Central Italy.